A Worldwide Epidemic: The Problem and Challenges of Preterm Birth in Low- and Middle-Income Countries - Smid, Marcela C.; Stringer, Elizabeth M.; Stringer, Jeffrey S. A. (American Journal of Perinatology, 2016)
Preterm birth (PTB) is the most common cause of neonatal death worldwide and the second leading cause of under-5 mortality. Low- and middle-income countries (LMICs) bear a disproportionate burden of this disease. An estimated 1 million preterm infants die in the neonatal period each year and many of those who survive face lifelong disability. In this review, we explore the global burden of PTB through an examination of risk factors and predisposing clinical conditions found in LMICs. We then discuss current interventions available to prevent PTB and/or mitigate its clinical sequelae. A major finding of this review is that although the majority of the global PTB disease burden is shouldered by LMICs, very little of the research evidence for its prevention and treatment derives from these settings. Primary research and implementation studies that involve LMIC populations are urgently needed.
Keywords: global health; preterm birth; prematurity; low- and middle-income countries